Ichthyofaunal Diversity in the Freshwater Tidal Stretch Along the Gosthani Estuary, Bheemunipatnam, Visakhapatnam, Andhra Pradesh, India - K. Rama Rao; V. Harati; R. Ramachandra Rao (Contemporary Research and Perspectives in Biological Science Vol. 4, 2024)
India’s east and west coasts are rich in estuaries and brackish water. According to the Government of India (2000), total brackish water resources are expected to reach 1.44 million hectares. Andhra Pradesh is divided into nine districts and has a 974-kilometer-long coastline and a continental shelf size of 33,227 square kilometers. The objective of this study was to follow the species observed in artisanal fisheries, offer important background information, and allow nonspecialists to identify the fish species in the field. In this study, fish samples were taken from the Gosthani estuary at Bhimunipatnam at 17.8961° N, 83.4545° E between April 2023 and August 2024. The present study found 60 fish species belonging to 16 orders, 34 families, and 54 genera in the Gosthani estuary between May 2023 and August 2024. The fish were brought to the lab and placed in glass jars before being preserved in a 9-10% formalin solution. The fishes were identified at the species level using specific keys to the Indian subcontinent fish. In the present investigation out of 60 brackishwater ichthyofauna species, the order Perciformes represented the highest species, with 46.66%, followed by Siluriformes 8.33%, Clupeiformes 6.66%, Beloniformes and Tetraodontiformes each with 5.71%, Anguilliformes, Carangiformes, Atheriniformes, Cypriniformes, Mugiliformes and Mulliformes each with 3.33%, The homogeneous percentage was recorded in Elopiformes, Gobiiformes, Gonorynchiformes, Osteoglossiformes, and Synbranchiformes each with 1.66%. According to the IUCN (2024) threatened taxa in the current investigation reveled that the presence of out of 60 species, 66.66% contributed to least concern (LC), followed by 21.66 % not evaluated (NE), 5.00% are data deficient (DD), 3.33% are near threaten (NT) and vulnerable (VU). In the current study, ichthyofaunal diversity reported to the habitation environment was observed in marine and brackish water fish species (76.66%), while brackish water and freshwater were inhabited (55.00%) in the Gosthani estuary. The study recorded the fish species diversity and prepared an inventory incorporating their trophic level and IUCN conservation status. This report provided first-hand information on ichthyofaunal diversity in the Gostani estuary. The different contributions of dominant species in each habitat resulted in variances in assemblage population.